Travelling to the Koinon Assembly – Provincial Level Elite Mobilization during the Principate. - 吴靖远 (15th TACMRS International Conference, 2021)
Koinon assemblies during the Principate were occasions when member communities dispatch delegations to gather at specifically designated cities, where they elect koinon officers and deliberate a range of affairs –– chiefly among which were festivities and sacrifices that honored the Roman emperors and the local cultic and civic traditions, but also revenues and expenditures, administrative tasks delegated by the imperial government, among others (Deininger 1965: 137-147; Edelmann-Singer 2015: 193-248, 309-310). Much has been discussed regarding the institutional aspects of the koinon assemblies; what could benefit from more discussion is the act of traveling to koinon assemblies. This paper assembles a small number of literary and epigraphic references that provide circumstantial references to koinon assembly-related travel anecdotes. Of particular importance among these are Strabo's description of the gathering of delegates from Lycian cities to the koinon meeting each year (Strab. 13.3.3), Aelius Aristides' account of the city of Smyrna's manipulative nomination of him as a candidate for the high priest of Asia (Ael. Arist. Hieroi Logoi 4.99-104), and the inscription honoring Quintus Popilius Python's gift to attendees of the koinon assembly while serving as the high priest of the Macedonian koinon (EKM 117). By assembling these and other evidence, this paper wishes to suggest that koinon assemblies were compulsory events that each member community would have to participate in, often at their own expense. Wealthy koinon-officeholders may opt to offset the burdens that communities (or their designated representatives) would have to shoulder in dispatching delegation, and such benefaction may be viewed from the perspective of a soft mobilization of the provincial elites in order to facilitate the orderly execution of business in the interest of the public weal.